Reducing dropout in distance education: A contextual approach - Tim Belawati (Adult Education Research Conference, 1995)
Dropout phenomenon needs to be understood within the context in which the problem occurs. This study tested the effectiveness of several institutional interventions in reducing early attrition in distance education within Indonesian context.